(untitled) (Journal of Contemporary Dental Sciences, 2026)
Background: Pregnancy is a critical period during which hormonal and behavioral changes increase susceptibility to various oral health problems. Poor oral hygiene and lack of awareness among pregnant women can exacerbate conditions such as gingivitis, tooth decay, and gum inflammation. Understanding the associations between oral health status and oral hygiene practices is essential to guide preventive care during pregnancy. Objectives: To assess the association between oral health status and oral hygiene behavior also practice among pregnant women attending hospitals in Bangladesh and to identify socio-demographic and behavioral factors influencing oral health problems. Materials and methods: A cross-sectional study was conducted among 206 pregnant women selected from different hospitals in Bangladesh. Data were collected through a pre tested structured questionnaire covering the socio-demographic characteristics, pregnancy-related information, oral hygiene practices, and self-reported oral health problems. Statistical analysis was performed using SPSS software, applying descriptive statistics and Chi-square tests to examine associations, with a significance level set at p < 0.05. Results: Overall, 69.3% of participants reported at least one oral health problem, most commonly tooth sensitivity (65.0%), tooth decay (53.4%), swollen gums (41.3%), painful or reddish gums (37.4%), gum bleeding (33.4%), and dental caries (26.7%). A significant association was observed between pregnancy trimester and gum problems—bleeding (p = 0.000), swollen (p = 0.015), painful (p = 0.031), and reddish gums (p = 0.001). Awareness about pregnancy gingivitis was significantly related to educational level (p = 0.036), while bleeding gums were associated with monthly income (p = 0.032). Brushing frequency (p = 0.010), type of cleaning material (p = 0.009), and frequency of consuming sugary foods (p = 0.004, p = 0.041) showed significant associations with different gum problems, whereas dental visit timing showed no significant relationship (p > 0.05). Conclusion: Oral health problems were highly prevalent among pregnant women and were significantly associated with pregnancy trimester, socioeconomic status, brushing habits, and dietary practices. Educational interventions and integration of oral health counseling into antenatal care are recommended to improve awareness and promote better oral hygiene behaviors during pregnancy. J. Contemp. Dent. Sci. 2026;14(1):14-17